CHIMERE-2017: from urban to hemispheric chemistry-transport modeling - Mailler, Sylvain; Menut, Laurent; Khvorostyanov, Dmitry; Valari, Myrto; Couvidat, Florian; Siour, Guillaume; Turquety, Solène; Briant, Régis; Tuccella, Paolo; Bessagnet, Bertrand; Colette, Augustin; Létinois, Laurent; et al. (Geoscientific Model Development, 2017)
CHIMERE is a chemistry-transport model designed for regional atmospheric composition. It can be used at a variety of scales from local to continental domains. However, due to the model design and its historical use as a regional model, major limitations had remained, hampering its use at hemispheric scale, due to the coordinate system used for transport as well as to missing processes that are important in regions outside Europe. Most of these limitations have been removed in the CHIMERE-2017 version, allowing its use in any region of the world and at any scale, from the scale of a single urban area up to hemispheric scale, with or without polar regions included. Other important improvements have been made in the treatment of the physical processes affecting aerosols and the emissions of mineral dust. From a computational point of view, the parallelization strategy of the model has also been updated in order to improve model numerical performance and reduce the code complexity. The present article describes all these changes. Statistical scores for a model simulation over continental Europe are presented, and a simulation of the circumpolar transport of volcanic ash plume from the Puyehue volcanic eruption in June 2011 in Chile provides a test case for the new model version at hemispheric scale.